2019
DOI: 10.1111/acel.13050
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome suppression improves longevity and prevents cardiac aging in male mice

Abstract: While NLRP3-inflammasome has been implicated in cardiovascular diseases, its role in physiological cardiac aging is largely unknown. During aging, many alterations occur in the organism, which are associated with progressive impairment of metabolic pathways related to insulin resistance, autophagy dysfunction, and inflammation.Here, we investigated the molecular mechanisms through which NLRP3 inhibition may attenuate cardiac aging. Ablation of NLRP3-inflammasome protected mice from age-related increased insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
108
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 145 publications
(119 citation statements)
references
References 48 publications
11
108
0
Order By: Relevance
“…Nlrp3 ablation also showed an increase in autophagy in aged ovaries consistent with previous data in other tissues (8,24). It is known that autophagy efficiency is reduced during aging in many tissues (25).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Nlrp3 ablation also showed an increase in autophagy in aged ovaries consistent with previous data in other tissues (8,24). It is known that autophagy efficiency is reduced during aging in many tissues (25).…”
Section: Discussionsupporting
confidence: 91%
“…Increased systemic inflammation is commonly associated with metabolic alterations, including the appearance of increased adiposity, insulin resistance, and dyslipidemia, responses that are likely critical determinants in the shortening of lifespan and overall health. Many of these metabolic alterations have been associated to NLRP3-inflammassome activation (1,(8)(9)(10). However, little is known about the role of NLRP3 during female aging and fertility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NLRP3-deficient mice have improved health span and attenuated age-related functional decline, including reduced bone loss, improved memory and cognitive performance, and motor performance (78). Recently, it was reported that aged NLRP3-deficient mice have reduced cardiac hypertrophy and fibrosis and increased life spans compared to wild type mice (14). This study linked the NLRP3-deficiency in aged mice to reduced mTOR suppression resulting in increased autophagic activity (14).…”
Section: Age-related Reduction In Autophagy and Mitophagymentioning
confidence: 91%
“…It is also a key pathway in cellular quality control by eliminating dysfunctional or unwanted organelles and protein aggregates. However, there is strong evidence that autophagy is decreased with age in tissues, including the heart (5,(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%